Main Thought of al Muhasibi in the Book al Masail fi A'mal al-Qulub wa al-Jawarih fi al Makasib wa al-Aql - Zaenudin Zaenudin; Ahmad Tantowi (The Institute of Research and Service Community IPMAFA Pati, 2022)
Al-Muhasibi was a phenomenal figure in the VIII-IX centuries who mastered several disciplines, especially fiqh and al-hadith as well as Sufism. Al-Muhasibi was born in Iraq in 781 AD (165 AH). His thoughts in the field of Sufism can be found in several of his monumental works, among others, in ar-Risalah lil Huquqillah, al-Washoya aw an-Nashoih, Risalah al-Mustarsyidin, al-Masail fi A'mal al Qulub wa al-Jawarih wa al- Makasib wa al-Aql and Fi Fahm al Qur'an (understanding the Koran). The book of al-Masail fi A'mal al-Qulub wa al-jawarih fi al-Makasib wa-al-Aql by al-Muhasibi essentially leads to spiritual education so that people are clean in mind, have a clear heart and sincerely seek forgiveness and love of Allah in their activities. The Methode used in this paper is qualitative content analysis. This book explaned about zuhud and keeping the body as good as possible to achieve the mercy and blessing from the God the almighty. al Muhasibi explained that people who have simple ideals will cause that person to have positive activities and always be zuhud in spending their assets. This is because, he is afraid that his property will be lost so that he cannot spend it according to Allah's command. al-Muhasibi's thoughts in his book al Masail fi A'mal al-Qulub wa al-jawarih fi al Makasib Wa al-Aql to be used as a qudwah (model) for human behavior. The behavior referred to here is both in the context of human interaction in the vertical dimension, namely interacting with God (Allah), as well as in the horizontal application level, namely human interaction with other humans.